Annual report for e-government 2005 (MOGAHA)
Contains the government's direction toward e-government, including vision and goals; introduces international trends and advanced cases with specific reference to the US and Australia. Describes in detail the businesses that each government office has pursued under the E-government roadmap.
Keywords: INTERNET